Integrating Single Atoms with Different Microenvironments into One Porous Organic Polymer for Efficient Photocatalytic CO2 Reduction - Dong, Xiao‐Yu; Si, Ya‐Nan; Wang, Qian‐You; Wang, Shan; Zang, Shuang‐Quan (Advanced materials (Weinheim), 2021)
The precise identification of single‐atom catalysts (SACs) activity and boosting their efficiency toward CO2 conversion is imperative yet quite challenging. Herein, for the first time a series of porous organic polymers is designed and prepared simultaneously, containing well‐defined M–N4 and M–N2O2 single‐atom sites. Such a strategy not only offers multiactive sites to promote the catalytic efficiency but also provides a more direct chance to identify the metal center activity. The CO2 photoreduction results indicate that the introduction of salphen unit with Ni–N2O2 catalytic centers into pristine phthalocyanine‐based Ni–N4 framework achieves remarkable CO generation ability (7.77 mmol g–1) with a high selectivity of 96% over H2. In combination with control experiments, as well as theoretical studies, the Ni–N2O2 moiety is evidenced as a more active site for CO2RR compared with the traditional Ni–N4 moiety, which can be ascribed to the M–N2O2 active sites effectively reducing the energy barrier, facilitating the adsorption of reaction radicals *COOH, and improving the charge transportation. This work might shed some light on designing more efficient SACs toward CO2 reduction through modification of their coordination environments. Single metal sites with –N4 and –N2O2 coordination mode simultaneously incorporated into one porous organic backbone are reported. With the assistance of experimental results and theoretical calculations, the –N2O2 coordinated single metal sites are identified with higher catalytic activity toward CO2 photoreduction compared to that of traditional –N4 coordinated one.